Efficacy and safety of uninterrupted low‐intensity warfarin for cryoballoon ablation of atrial fibrillation in the elderly: A pilot study. (26th February 2018) - Xing, Y.; Xu, B.; Sheng, X.; Xu, C.; Peng, F.; Sun, Y.; Wang, S.; Guo, H.
Summary: What is known and objective: Uninterrupted warfarin during cryoballoon ablation (CB‐A) of atrial fibrillation (AF) has been widely accepted. However, to our knowledge, no previous studies exist investigating the optimal intensity of anticoagulation with warfarin for CB‐A. This study aimed to evaluate the efficacy and safety of uninterrupted low‐intensity warfarin for CB‐A of AF in the elderly. Methods: Paroxysmal AF patients (age ≥ 70 years) who underwent CB‐A were enrolled prospectively. The participants were stratified into 2 groups based on international normalized ratio (INR) before ablation (INR in group A: 1.5 to 2.0; INR in group B: 2.0‐2.5). Primary endpoints included periprocedural thromboembolic complications and major bleeding. Secondary endpoints were new asymptomatic cerebral emboli (ACE) and minor bleeding. Results and discussion: A total of 144 patients were enrolled (group A: 65; group B: 79). In group A, the use of concomitant antiplatelet drugs was more common. Also, the mean HAS‐BLED score was significantly higher (2.4 ± 0.8 vs 2.0 ± 0.6, P  < .01) and the mean activated clotting time (ACT) during the procedure was significantly lower (302 ± 14 s vs 311 ± 11 s, P  < .01). Other clinical characteristics were balanced between the 2 groups. No thromboembolic complications and major bleeding occurred in either group. The incidence of periprocedural ACE was comparable between the 2 groups (9.2% vs 6.3%, P  = .74). The incidence of minor bleeding in group A and group B was 4.6% and 11.4%, respectively ( P  = .14). What is new and conclusion: Compared with standard‐intensity warfarin, uninterrupted low‐intensity warfarin might not increase the incidence of thromboembolic complications and might be associated with less bleeding risk during the perioperative period of cryoballoon ablation in the elderly. Large trials are needed to confirm these results.